Towards the development of an acceptable and user-friendly self-sampling intervention for diagnosing sexually transmitted infections among young women in eThekwini District Municipality, South Africa - Mashamba‑Thompson, Tivani Phosa (University of Pretoria, 2025)
Thesis (PhD (Public Health))--University of Pretoria, 2024.